Plasma levels of endothelial and B-cell-derived microparticles are restored by fingolimod treatment in multiple sclerosis patients. (December 2016) - Zinger, Anna; Latham, Sharissa L; Combes, Valery; Byrne, Scott; Barnett, Michael H; Hawke, Simon; Grau, Georges E
Background: No molecular marker can monitor disease progression and treatment efficacy in multiple sclerosis (MS). Circulating microparticles represent a potential snapshot of disease activity at the blood brain barrier. Objectives and methods: To profile plasma microparticles by flow cytometry in MS and determine how fingolimod could impact endothelial microparticles production. Results: In non-treated MS patients compared to healthy and fingolimod-treated patients, endothelial microparticles were higher, while B-cell-microparticle numbers were lower. Fingolimod dramatically reduced tumour necrosis factor (TNF)-induced endothelial microparticle release in vitro. Conclusion: Fingolimod restored dysregulated endothelial and B-cell-microparticle numbers, which could serve as a biomarker in MS.